FROM CONTESTATION TO CONSENSUS: Religious Authority and the Making of Islamic Moderation in Post-Padri War Minangkabau, 1830–1869 - Yudhi Andoni; Yon Machmudi; Abdurakhman Abdurakhman (State Islamic University North Sumatra, 2026)
Contemporary scholarship on Islamic moderation has largely emphasized normative doctrines, state policies, and institutional reforms, while paying limited attention to the historical social processes through which moderation emerged in post-conflict Muslim societies. This article examines the reconstruction of religious authority and social reconciliation in Minangkabau following the Padri War (1830–1869), focusing on the role of Surau Calau as a center of intellectual and social transformation. Employing a social-historical approach combined with philological analysis of Jawi manuscripts, the study investigates the interaction between the surau institution, local textual traditions, and the leadership of Sheikh Abdul Wahab Calau in shaping a contextually grounded model of Islamic authority. The findings identify three interconnected processes. First, Surau Calau functioned as an inclusive social space that fostered hybrid religious authority and mediated post-war ideological divisions within Minangkabau society. Second, Jawi manuscripts facilitated intellectual vernacularization by translating Islamic metaphysical and ethical concepts into locally intelligible agrarian analogies, enhancing their cultural resonance and social acceptance. Third, reconciliation was institutionalized through collaboration between religious scholars and traditional chiefs in educational governance and communal rituals, creating a durable framework for social cohesion. The study argues that Islamic moderation emerged through negotiated authority, vernacular knowledge production, and cross-communal cooperation, offering broader insights into post-conflict reconciliation and religious coexistence in plural societies.